METHODOLOGY OF STATISTICAL ANALYSIS, SHORT-TERM FORECASTING OF INDUSTRIAL INJURIES AND WAYS OF THEIR PREVENTION IN AGRO-ENGINEERING - Kostenko, O. M.; Lapenko, T. G.; Opara, N. M.; Dudnyk, V. V.; Shpylka, M. M.; Drozhchana, O. U. (Scientific Progress & Innovations, 2021)
Extremely intensive development of production in practically all countries, including Ukraine, is accom-panied by such negative phenomena as industrial injuries and professional diseases. It is well known that there are many sources and reasons proceeding the occurrence of industrial injuries and professional dis-eases, including organizational, engineering, technical, sanitary, hygienic, regulatory and legal, etc. Accord-ing to the data of the International Labor Organization, the number of work-related injuries in Ukraine is one of the highest among European countries. The death-rate from industrial injuries takes the third place after cardio-vascular and oncological diseases. The presented indicators show the extreme importance of industrial injuries’ problem, therefore the topic requires solving. A number of researches connected with the above mentioned problem have been conducted by scholars in our country; the results of these studies are used in developing ways to prevent accidents at work. In spite of the considerable scientific and practical contribution of the researchers in studying various aspects of industrial injuries and developing preventive measures at the state and enterprises’ level, this problem remains topical in Ukraine and requires innovative, scientifically substantiated approaches to its solving. It should be stressed that the problem of decreasing the level of work-related accidents is considered to be the category of particular state and social importance, and its solving is the priority task of Ukraine’s national security. The analysis of industrial ac-cidents in this country is one of the main and necessary ways to develop the mechanisms of preventing and avoiding industrial injuries. Moreover, different methods and techniques of analysis, such as statistical, monographic, economic, ergonomic, and others are used. The methodology of analysis, short-term forecast-ing of industrial injuries and ways of their prevention has been proposed in the article, which enables to de-tect the expected picture of phenomena and get the prognosticated models for the dynamics of industrial ac-cidents’ indicators that are the basis for developing the ways of work-related accidents’ prevention.